Full Genomic Characterization of a Lentogenic Newcastle Disease Virus Isolated from Farm-Reared Ostriches (Struthio camelus) in Northwest China - Ren, Shanhui (Genome Announc, 2017)
To our knowledge, our study is the first to report the whole-genome sequence of an ostrich-origin Newcastle disease virus (NDV) isolate, abbreviated as Ostrich/SX-01/06. Phylogenetic analysis revealed that this isolate belongs to the subgenotype c in class II. The identification of the complete genome will provide useful information regarding ostrich diseases, especially NDV.